Profile and generalist physician knowledge about neurology in emergency department: headache management - MORAES E SILVA, Maren de; SCHULTZE, Arnon César Brunet; CAVALHEIRO, Beatriz Pyrich; MEYER, Lucas Filadelfo; FRONCHETTI, Juliana de Andrade; MERCER, Pilar Bueno Siqueira; WITT, Maria Carolina Zavagna (Arquivos de Neuro-Psiquiatria, 2020)
Background: Neurological complaints are frequent in emergency department routine. Among them, headache is a common disorder, which requires a certain degree of knowledge on Neurology because of its extensive differential diagnosis. Objective: To assess general practice physicians’ level of knowledge about headaches, in addition to outlining the profile of professionals who attend in emergency departments, as well as the profile of their respective workplaces in terms of neurological approach. Methods: We included in evaluation physicians who attend emergency care units for adult public as general practitioners. A questionnaire was applied with questions regarding participants’ general knowledge on headache, neurological approach, demographic profile, and workplace profile. Results: 159 physicians answered the questionnaire. The professionals’ profile corresponded to recently graduated individuals (mean of 6.31 years). Knowledge about headache management was regular. Those who do not have any specialization or are not majoring a specialization were statistically significantly more confident in neurological patients care (p=0.006). Only 18.24% reported access to Magnetic Resonance Imaging and 35.85% had no access to any type of neuroimaging. Conclusions: General practice physicians often do not feel confident when performing neurological exams, demonstrating low knowledge about the topic. The profile of professionals working in these departments is predominantly of newly graduates, which may affect in some way on care quality. There was also a lack of structure for adequate care.
Keywords: headache; knowledge; general practitioners; neurology; emergency medical services